Single-Stage Versus 2-Stage Bilateral Intramedullary Nail Fixation in Patients With Bilateral Femur Fractures: A Multicenter Retrospective Review. Issue 9 (September 2021) - Flagstad, Ilexa R.; Tatman, Lauren M.; Heare, Austin; Parikh, Harsh R.; Albersheim, Melissa; Atchison, Jared; Breslin, Mary; Davis, Patrick; Feinstein, Shawn; Hak, David J.; Labrum, Joseph T.; Lufrano, Reuben C.; et al.
Abstract : Objective: To evaluate rates of complications in patients with bilateral femur fractures treated with intramedullary nailing (IMN) during either 1 single procedure or 2 separate procedures. Design: A multicenter retrospective review of patients sustaining bilateral femur fractures, treated with IMN in single or 2-stage procedure, from 1998 to 2018 was performed at 10 Level-1 trauma centers. Setting: Ten Level-1 trauma centers. Patients/Participants: Two hundred forty-six patients with bilateral femur fractures. Interventions: Intramedullary nailing. Main Outcome Measures: Incidence of complications. Results: A total of 246 patients were included, with 188 single-stage and 58 two-stage patients. Gender, age, injury severity score, abbreviated injury score, secondary injuries, Glasgow coma scale, and proportion of open fractures were similar between both groups. Acute respiratory distress syndrome (ARDS) occurred at higher rates in the 2-stage group (13.8% vs. 5.9%; P value = 0.05). When further adjusted for age, gender, injury severity score, abbreviated injury score, Glasgow coma scale, and admission lactate, the single-stage group had a 78% reduced risk for ARDS. In-hospital mortality was higher in the single-stage cohort (2.7% compared with 0%), although this did not meet statistical significance ( P = 0.22). Conclusions: This is the largest multicenter study to date evaluating the outcomes between single- and 2-stage IMN fixation for bilateral femoral shaft fractures. Single-stage bilateral femur IMN may decrease rates of ARDS in polytrauma patients who are able to undergo simultaneous definitive fixation. However, a future prospective study with standardized protocols in place will be required to discern whether single- versus 2-stage fixation has an effect on mortality and to identify those individuals at risk. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.